Advances in Understanding the Causes, Molecular Mechanism, and Perspectives of Russeting on Tree Fruit - Jiang, Shenghui; Chen, Min; Wang, Ziqi; Ren, Yanxue; Wang, Bin; Zhu, Jun; Zhang, Yugang (Frontiers in Plant Science, 2022)
The external quality of fruit is one of its most important qualities; good external quality attracts consumers easily and increases the value of fruit. Fruit russeting is one of the factors that influences the external quality of fruit and has been studied in most horticultural plants. However, the molecular mechanism of russeting has never been discussed so far. In this review, we summarize the research progress on fruit russeting, including causes, microscopic histomorphology, composition, genetics, and regulation and made a series of elaboration on the current research on fruit russeting. This study aims to provide insights into the mechanisms underlying fruit russeting. It also puts forward ideas for research on fruit russeting, which may provide a reference for future research.